2021
DOI: 10.1097/pq9.0000000000000492
|View full text |Cite
|
Sign up to set email alerts
|

Quality Improvement Initiative to Improve Hand Hygiene Compliance in Indian Special Newborn Care Unit

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Most published intervention studies from neonatal units report substantial HH compliance improvements, but the seldom report on impact on neonatal HA-BSI rates. A study from a Special Neonatal Care Unit in India demonstrated an improvement of 30% in mean HH compliance following the implementation of HH posters, HH educational sessions, provision of HH consumables, and weekly performance feedback and discussions [ 39 ]. A Ghanaian neonatal ICU achieved improved HH compliance from 67% to 92% compliance with training, practice reinforcement, visual reminders, and continuous provision of HH consumables [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most published intervention studies from neonatal units report substantial HH compliance improvements, but the seldom report on impact on neonatal HA-BSI rates. A study from a Special Neonatal Care Unit in India demonstrated an improvement of 30% in mean HH compliance following the implementation of HH posters, HH educational sessions, provision of HH consumables, and weekly performance feedback and discussions [ 39 ]. A Ghanaian neonatal ICU achieved improved HH compliance from 67% to 92% compliance with training, practice reinforcement, visual reminders, and continuous provision of HH consumables [ 40 ].…”
Section: Discussionmentioning
confidence: 99%